New Dynamics of Disability and Rehabilitation Interdisciplinary Perspectives - Harsløf, Ivan; Poulsen, Ingrid; Larsen, Kristian (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This collection provides a broad coverage of recent changes in medical and vocational rehabilitation in Northern Europe. It presents analyses that cut across health sciences, medical sociology, disability studies and comparative welfare state research. Through this interdisciplinary perspective, the book explores the changing roles of patients, caregivers, professionals and institutions, and the wider implications of these changes for social inequalities in health. What obstacles do different groups of patients encounter when negotiating the complex chains of medical and vocational services? Who decides regarding references to specialized treatments, and the provision of comprehensive and coordinated services, and different types of benefits and material support? What is the importance of the resources that patients and caregivers bring to bear in the rehabilitation process?